EL DESARROLLO DE COMPETENCIAS LABORALES Y LA fORMACIÓN DE LOS PROfESIONALES EN TURISMO EN LA UNIVERSIDAD NACIONAL MAYOR DE SAN MARCOS, AÑO 2013 - Granados Maguiño, Mauro Amaru (2013)
The objective of our research is to determine the relationship between the development of work competencies, as well as the apprenticeship of tourism professionals of the National University of San Marcos during 2013. The research demonstrates that of the analyzed students total, 54.17% has a good perception about basic competencies, 67.71% considers that generic competencies are good and 58.33% thinks that specific competencies are good. We as professors should have into account that student must acquire updated knowledges of the variety of tourism areas (universality). In addition, we have to develop capacity to understand systematically relevant information, its context and how to apply this information to complex situations (information domain). Moreover, to domain enough technics to obtain and analyze information, to synthetize and adapt it according to the context in technification.